Shareholder's Agreement or Disagreement: A Case Study of Cobalt Telephone Technologies Ltd (Parts I & II) - Brown, Robert (Senate Hall, 2007)
This two part case outlines how this new technology company was founded with minimal financial assets in 1997. Cobalt grew through developing an innovative market penetration strategy for its automated telephone response technology ("piggy-backing" by supporting established sector sub-contractors), despite the creation of unnecessary 'financial risk' by an overly generous "kitchen-table" early share allocation, without a detailed share allocation agreement. Part I details the early educational and army career of Harry Clarke, together with his work experiences and frustrations with the Mercury and Automobile Association companies which led to the creation of Cobalt. Harry and his partner Peter, with high ethical standards and little finance, agreed to a generous share split at the outset and preferred to avoid extra legal expense which could have been incurred with a more detailed shareholder agreement. The difficulties this decision created, relevant to many new companies, only became apparent when Peter decided to leave Cobalt in the middle of 'make or break' contract negotiations with the Manchester United Football Club. Students are invited to determine how shares in this still loss-making company should be valued and how all sides, inside and externally in the contract negotiations, should conduct themselves. In Part II, the faster growth of Cobalt is detailed as the company benefited from the end of the 'Dot-Com' boom, by acquiring 'knock-down' computer and telephone assets from collapsed new technology enterprises. This enabled Cobalt to develop more constant revenue streams through 'the hosting' at its own premises of automated car-parking fines for local public authorities throughout the UK. In 2005, after 8 exhausting years, Peter, who had, six months after leaving, returned to help Cobalt complete the Manchester United contract, (for automated telephone ticket sales) once again decided he wanted to resign. With the company now profitable, students are again invited to decide how shareholdings should be valued and how both partners should prepare for a final settlement meeting.
Keywords: entrepreneurship|partnerships|shareholder agreements|start-up valuations|ethical decisions